1997
DOI: 10.1177/000456329703400307
|View full text |Cite
|
Sign up to set email alerts
|

One-Step Enzyme-Linked Immunosorbent Assay (ELISA) for Plasma Fatty Acid-Binding Protein

Abstract: SUMMARY. To allow a more rapid determination of heart-type fatty acid-binding protein (FABP) concentration in plasma a direct non-competitive (sandwich-type) ELISA was developed which uses high-affinity monoclonal antibodies to FABP. Total performance time of the one-step immunoassay is 45 min. The standard curve was linear between 0·2-6/lg/L, and the within-run and between-run coefficients of variations were below 6 and II %, respectively. The serum FABP concentration measured in 79 healthy individuals was 1·… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
50
0
1

Year Published

2000
2000
2021
2021

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 104 publications
(54 citation statements)
references
References 17 publications
3
50
0
1
Order By: Relevance
“…The homogenates were subsequently sonicated four times for 15 s each time and centrifuged at 10,000 ϫ g for 2 min at 4 C to remove cell debris. The tissue content of heart-type or muscle-type FABPc in skeletal muscle was measured by means of a newly developed enzyme-linked immunosorbent assay (Hycult Biotechnology, Uden, The Netherlands), using recombinant human FABP as standard (24). Citrate synthase was determined according to the method of Shepherd and Garland (25), whereas 3-hydroxyacyl-coenzyme A dehydrogenase was assayed according to the method of Bergmeyer (26).…”
Section: Biochemical Methodsmentioning
confidence: 99%
“…The homogenates were subsequently sonicated four times for 15 s each time and centrifuged at 10,000 ϫ g for 2 min at 4 C to remove cell debris. The tissue content of heart-type or muscle-type FABPc in skeletal muscle was measured by means of a newly developed enzyme-linked immunosorbent assay (Hycult Biotechnology, Uden, The Netherlands), using recombinant human FABP as standard (24). Citrate synthase was determined according to the method of Shepherd and Garland (25), whereas 3-hydroxyacyl-coenzyme A dehydrogenase was assayed according to the method of Bergmeyer (26).…”
Section: Biochemical Methodsmentioning
confidence: 99%
“…Tissue content of heart-type or muscle-type cytoplasmatic fatty acid-binding protein (FABP) in skeletal muscle was measured by means of a newly developed ELISA, using recombinant human FABP as standard [30].…”
Section: Methodsmentioning
confidence: 99%
“…Since intestinal samples contained both enterocytes and myocytes, we also measured H-FABP as a marker of muscle content with a direct non-competitive sandwich-type ELISA using monoclonal antibodies obtained from Hycult biotechnology (HK 403; Uden, the Netherlands) as described previously [76]. These data showed significantly higher H-FABP in jejunum (1.7360.30) as compared to duodenum, ileum (1.0960.19), proximal colon (0.9760.16) and distal colon (0.9060.17), Because of this, we concluded that the biopsy muscle content was for an unknown reason higher in our jejunum biopsies and this might have resulted in an underestimation of cholesterol transport protein levels, which are only expressed in enterocytes.…”
Section: Standardizationmentioning
confidence: 99%